Combination of Cognitive and Quantitative Aspects to Estimate the Degree of Emotions - Nguyen, Manh Hung (Journal of Computer Science and Cybernetics, 2017)
Emotions play a more and more important role in many fields of computer sciences such as ambient intelligence, interaction human - machine, affective computing, etc. This paper firstly constructs a logical framework to represent the qualitative cognitive factor of emotion based on a logic of belief and a logic of time. Secondly, it constructs a hedge algebra and its extension with fuzzy logic to represent the quantitative factor of emotions. These two aspects of emotion are then combined to estimate the degree of emotions based on the degree of their cognitive factors.